Factors associated with interstitial lung disease in patients with rheumatoid arthritis - Benyapa Suppa-Udom; Supparerk Disayabutr; Suwimon Wonglaksanapimon; Krittachat Butnian; Wanruchada Katchamart (Exploration of Musculoskeletal Diseases)
Aim: Interstitial lung disease (ILD) is a significant extra-articular manifestation of rheumatoid arthritis (RA). The prevalence and risk factors for ILD in RA exhibit considerable variation. This study aimed to determine the prevalence and factors associated with ILD in Thai patients with RA. Methods: This cross-sectional study enrolled 290 RA patients from the Siriraj Rheumatoid Arthritis Registry between March and December 2022. Patient characteristics, disease activity and functional status were documented. Chest radiography (CXR) was employed for ILD screening, and suspected cases were further evaluated using high-resolution computed tomography (HRCT) and pulmonary function tests. Two radiologists independently analyzed CXR and HRCT images, with any discrepancies resolved by a pulmonologist. Results: Among the 290 patients, the majority were female (89.7%) with mean age (SD) of 58.8 (11.5) years, and the median disease duration was 10 years (range 6–17 years). Patients exhibited low disease activity [mean Disease Activity Score 28-erythrocyte sedimentation rate score (SD) 2.69 (0.90)] and mild functional impairment [median Health Assessment Questionnaire score (range) 0.25 (0–0.63)]. Thirteen patients (4.5%) were diagnosed with ILD via HRCT (RA-ILD), with nonspecific interstitial pneumonia being the predominant ILD pattern (69.2%). Pulmonary function tests showed normal results in most patients, with only 15.5% presenting restrictive ventilatory defects. Age (P = 0.04), breathlessness (P < 0.001), crackles (P < 0.001), and functional impairment (P = 0.02) exhibited significant associations with RA-ILD. Conclusions: ILD is relatively infrequent in Thai patients with RA. However, older age, breathlessness, crackles, and functional impairment should prompt investigations for ILD in RA patients.